Study of Bunch Fresh Palm Drying by Solar Energy - เทพษร, พงศกรณ์ (Princess of Naradhiwas University Journal, 2018)
This research investigated and designed a drying plant for bunch fresh palm using solar energy. The dimension of the solar panel plant was 2 × 5.5 × 1 meter (wide x long x high) with curved roof sheet and wall were made from polycarbonate sheet receiving the thermal radiation and occurring greenhouse effect inside the pant. All side walls are made from polycarbonate sheets for insulation. A long side wall was a door used to open and close and other three sides were sealed. The suction fans were installed at the front and rear walls in order to remove the moisture to outward. To prevent floor of the factory damage, a smart board with a thin aluminium was used to prevent moisture. The outside design of the plant is high from ground around 0.5 meter. The results of the experiment showed that the internal temperature of the plant was between 38 to 70 °C. The internal air humidity was between 36 to 46 %. Regarding the falling rate of fresh fruit bunch during one to five days of drying of palm fruit in a solar-powered plant, the average falling rate was around 20 to 26%. In addition, on day 6-7, the average fall of fresh fruit bunch was between 7 to 14%.Finally, the total oil content of the seven days was 187 to 260 ml per 1 kg palm fruit. However, the fatty acid during day 1-2 increased free fatty acid, which was averaged between 10.39 to 10.51 wt.% and on day 3 to7 reduced between 1.35 to 2.97 wt%.